Specialised for the Swamp, Catered for in Captivity? A Cross-Institutional Evaluation of Captive Husbandry for Two Species of Lechwe - Paul E. Rose; Lewis J. Rowden (Animals, 2020)
Lechwe are specialised wetland antelope that can have a strict social hierarchy or perform lekking during breeding. The southern lechwe (Kobus leche) and the Nile lechwe (K. megaceros) are both found in zoos globally, but little research is available to support husbandry decisions. The aim of this research was to investigate current housing and husbandry used for these lechwe across North American and European zoos. A survey was distributed to holders in 2018 and information on 33 herds (18 Nile and 15 southern) was collected. The survey focussed on population demographics, enclosure size, biologically relevant exhibit features, mixed-species holdings, nutrition, use of environmental enrichment and performance of abnormal repetitive behaviours. Results showed that lechwe were housed in herds with similar sex ratios to wild counterparts but with a potential lack of opportunity to lek. Many zoos provided wetland, but this was rarely actively managed, and not all zoos provided cover for hiding and retreat. Current feeding practice differed significantly compared to available antelope husbandry guidelines. No consistency in amounts of pellet, forage or produce provided to lechwe across institutions was found. Abnormal repetitive behaviour was noted by several zoos, but no significant predictor of such behaviour could be identified. Despite some identifiable recognition of ecology informing lechwe management, it is important that evidence-based husbandry decisions are made based on a species’ evolutionary pathway and ecological needs and some fundamental features of lechwe husbandry do not always correlate with the adaptive traits of a specialised wetland ungulate.